2022
DOI: 10.3390/cryst12030379
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Coloration Mechanism in Violet-Red Pyrope-Almandine

Abstract: The most common type of garnet is pyrope-almandine, whose color varies from red to violet. In this study, 36 faceted gem-quality samples are used for electron microprobe, infrared spectrum, and UV-Visible spectrum test to find the coloration mechanism and spectroscopic characters in red-violet pyrope-almandine. The gradually increasing content of Mg2+ at the X position in the lattice is connected to the variation in the infrared spectrum. The wavenumber increases with the decrease of cationic radius, which mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…When the transmittance of the two regions is almost the same, the color of the gem is determined by the external light source. The absorptions at 573 nm and 569 nm correspond to the spin-forbidden transitions ( 5 E g → 3 T 1g and 5 E g → 3 E 1g , respectively) of eightfold-coordinated high-spin Fe 2+ , and Fe 3+ may have a contribution to these absorption bands [25,[28][29][30][31]. The unusual high-intensity spin-forbidden optical transitions of eightfold-coordinated Fe 2+ cause many optical transitions in the green-yellow part of the visible spectrum and leave two strong transmission windows in the green and red spectral regions.…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…When the transmittance of the two regions is almost the same, the color of the gem is determined by the external light source. The absorptions at 573 nm and 569 nm correspond to the spin-forbidden transitions ( 5 E g → 3 T 1g and 5 E g → 3 E 1g , respectively) of eightfold-coordinated high-spin Fe 2+ , and Fe 3+ may have a contribution to these absorption bands [25,[28][29][30][31]. The unusual high-intensity spin-forbidden optical transitions of eightfold-coordinated Fe 2+ cause many optical transitions in the green-yellow part of the visible spectrum and leave two strong transmission windows in the green and red spectral regions.…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
“…Very small amounts (<1 ppm) of Cr may be present in the samples. The weak absorption bands at 620 nm and 621 nm are both ascribable to Fe, and the spin-forbidden transitions of Cr 3+ ( 4 A 2g → 4 T 1g ) may have a slight contribution to these absorption bands [5,13,26,30,32]. The Fe 2+ spin-forbidden transition ( 5 E(D) → 3 T 1 (H)) produces a broad absorption band in the visible-light range 550-650 nm, leading to two transmittance regions on both sides, which show a yellowish green to brown alexandrite-like effect along with the change in the spectral power distribution of the light source.…”
Section: Uv-vis-nir Spectroscopymentioning
confidence: 99%
“…Qiu et al examined the causes of the color change in pyrope-spessartine garnets and discussed the color of garnet samples that different kinds of light source cause [18]. Yang et al found the new coloration mechanism of violet-red pyrope-almandine [19]. Lv et al analyzed how gemstones' composition affects their color parameters, finding the genesis of the body color of opal [20].…”
Section: Introductionmentioning
confidence: 99%